Helmintos parasitando anuros em poças ao longo de campos nativos do bioma Pampa brasileiro - Portela, Aline Aparecida Bastos (2021)
South Brazilian grasslands harbor about 80 native species of anurans associated with different phytophysiognomies, and an important species portion is considered restricted to this ecosystem type. However, the knowledge of the helminth community associated with anuran amphibians in the Pampa biome is restricted to the Argentine and Uruguayan Pampas, while lacks basic information about this group in the Brazilian Pampa. This knowledge gap motivated the development of the present study, aiming to contribute to the knowledge of the anuran helminth fauna along the native grasslands of the Brazilian Pampa. Thus, we: (1) describe the composition of the helminth community, the parasitic metrics, and the helminth infection organs in eight anuran species along the Pampa biome; (2) we investigated the relationship of environmental variables with variation in parasitic metrics and with the structure of helminth communities in anurans along the biome; (3) we tested the influence of environmental descriptors and host anuran characteristics on the functional diversity of helminths. The anurans were sampled using the 'survey at breeding sites' method in 40 ponds, in the spring and summer of 2017, 2018 and 2019. The sampling was carried out in grassland areas along the Pampa biome, inserted in four different physiographic regions of the biome in the Rio Grande do Sul: Coastal Plain, Cuesta de Haedo, Central Depression, and Sul-Rio-Grandense Plateau. We found 28 taxa of helminths belonging to Nematoda, Trematoda (Digenea), Cestoda, and Acanthocephala, distributed in the eight host anuran species. Of the 28 registered taxa, 22 are new registrations for this geographic region. Our results revealed that the pond spatiality was not related to the variation in any of the metrics of parasitic infection of the host anurans, but explained part of the variation in the structure of the helminth community in some hosts. Local and landscape variables were important to explain part of the variation in the structure of the helminth community and in the parasitic metrics. Water temperature positively influenced the functional diversity of helminths. Furthermore, we found a significant correlation between water temperature and some of the helminth functional traits: 'oral and cutaneous' mode of transmission, the average intensity of infection, and the indirect life cycle. Thus, our analyzes suggest that environmental variables at different scales influence the structure of the helminth community and parasitic metrics, but that those at a local scale are preponderant. Our results demonstrate the importance of the heterogeneity of the ponds on the structure of the helminth community and the parasitic metrics of anurans in the Pampa, contributing to the knowledge of the abiotic processes involved in the structuring of helminth communities.